Influence of temperature and substrate on germination and vigor of Jacaranda michantra Cham. - Bovolini, Marciéli Pitorini; Maciel, Caciara Gonzatto; Brum, Daniele Lemos; Muniz, Marlove Fátima Brião (Revista de Ciências Agroveterinárias, 2015)
The caroba (Jacaranda micrantha Cham.) is a forest species belonging to the family Bignoniaceae, with the potential for landscaping and commercial plantations, as well as recovering degraded areas. Due to limited information of listed species, the present study aimed to evaluate the effect of temperature and substrate suitable for seed germination. The experimental design was completely randomized in a 4 x 4 factorial, consisting of combinations of four temperatures (20, 25, 30 and 25-30 °C) and four substrates (sand, commercial substrate, vermiculite and Germitest® paper), with four replicates of 25 seeds each. The parameters evaluated were speed index of germination, first count germination, germination, length of seedlings, fresh weight and dry weight of normal seedlings. There was no difference between the substrates and temperatures tested in this study, for seed germination of J. micrantha. The 25 °C temperature, 30 °C and 25-30 °C combined with the substrates, sand and Germitest® paper are suitable for the germination of Jacaranda micrantha seeds, providing, in general, higher germination speed index values and seedling development.